THE EVALUATION OF FUNCTIONAL STATE OF A HAND AFTER SURGICAL RESTORATION OF THE FLEXOR TENDONS AT THE FIBRO-OSSEOUS CANALS - I. V. Popov (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
Till these days the problem of restoration of the function of damaged flexor tendons of fingers is unsolved. A.M. Volkova consider that none of the surgical department has so many disappointments of unsatisfactory results as in surgery of wrist flexor. Functional result of treatment is defined by: 1) the level of damage; 2) means suture; 3) suture material. Active role of a hand in human activity defines high frequency of damages of this segment. More often 1-2 zone subjected to trauma, it is connected with involuntary defensive reaction at the moment of trauma. The most difficult is to restore flexor tendons at the level of bone and fibrous channels. In this work the analysis of further results of treatment of patients had surgery of tendon unit in the department of microsurgery is given. On the basis of the findings optimal and promising areas for surgery technics and results of treatment improving are defined.